2007
DOI: 10.1016/j.biomaterials.2007.01.038
|View full text |Cite
|
Sign up to set email alerts
|

The differential influence of colocalized and segregated dual protein signals on neurite outgrowth on surfaces

Abstract: We present an in vitro micropatterning approach in which the density and spatial presentation of two separate protein layers can be independently controlled to form cell stripe assays through (1) the simultaneous application of microcontact printing (μCP) and microfluidic network patterning (μFN) to generate alternating stripes of pure single protein layers or (2) through μCP onto a pre-adsorbed homogeneous protein layer to generate alternating single and dual protein stripes. This approach enabled the creatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
(43 reference statements)
2
26
0
Order By: Relevance
“…In addition, it appears that little information is available to accurately predict the effect of laminin deposition through soft lithography techniques on its growth promoting activity. In an effort to address these shortfalls, we have developed a set of cell choice stripe assays in order to separate CSPG-laminin interactions from possible intrinsic effects that CSPGs may exert on neuronal cell attachment and neurite outgrowth [120,125]. Additionally, antibody attachment to a laminin epitope known to promote neuronal cell attachment and neurite outgrowth was used to relate the method of laminin deposition to resulting bioactivity [120,125].…”
Section: Protein Patterns and Cell Choice Assays In Studying Neuronalmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it appears that little information is available to accurately predict the effect of laminin deposition through soft lithography techniques on its growth promoting activity. In an effort to address these shortfalls, we have developed a set of cell choice stripe assays in order to separate CSPG-laminin interactions from possible intrinsic effects that CSPGs may exert on neuronal cell attachment and neurite outgrowth [120,125]. Additionally, antibody attachment to a laminin epitope known to promote neuronal cell attachment and neurite outgrowth was used to relate the method of laminin deposition to resulting bioactivity [120,125].…”
Section: Protein Patterns and Cell Choice Assays In Studying Neuronalmentioning
confidence: 99%
“…It was found that the activity of substrate bound laminin on glass differed whether it was adsorbed from a solution, using microfluidic networks patterning, or transferred by microcontact printing, and that laminin conformation, as measured by integrin presentation, was a strong predictor of neuronal cell adhesion and neurite outgrowth behavior [120,125]. It was additionally observed that the order in which laminin and the CSPG aggrecan were adsorbed onto glass clearly affected laminin activity, suggesting interactions between CSPGs and laminin.…”
Section: Protein Patterns and Cell Choice Assays In Studying Neuronalmentioning
confidence: 99%
See 2 more Smart Citations
“…14,36,37 This study is part of a larger project aimed at understanding neuronal pathfinding dynamics on patterned biomaterials displaying two or more ECM proteins to modulate axonal growth. Allowing the axons to choose between more permissive and less permissive substrates may be a way to control the nerve's transition across an unfavorable boundary (e.g., the glial scar), which may be encountered by a regenerating neuron after a spinal cord injury (SCI).…”
Section: Introductionmentioning
confidence: 99%